Prevalence of use of dietary supplements between practitioners of physical activity in academies of two cities in the Vale do Aço-MG: Associated factors - Costa, Débora Cristina (2013)
The number of academies in Brazil is growing constantly and parallel to this, the food supplements are increasingly being used by its frequenters. The objective of this study was to identify the prevalence of the consumption of food supplements for individuals practicing physical activity in academies in two cities in the Valley of Steel, MG, and its associated factors. A research was conducted in September andOctober 2012, which applied a questionnaire containing 17 questions on the use of food supplements and its associated factors in nine academies. The sample was composed of 368 goers of the academies, being divided into two groups: users (40.2 %) and non users (59.8 %) of food supplements. In relation to age there was significant difference between the groups, with lower median for the group of users. In the group of non users, 56.0 % were female and practiced physical activity there is less than six months. Between the users 75.0 % were male, 47.0 % practiced physical activities there more than two years, and the bodybuilding to the more practiced (50.9 %).The supplement was the most common Whey Protein (20.0 %). The main purpose for the use of supplementshas been the gain of muscle mass (33.8 %), and 91.2 % showed satisfaction with the use of the product. It was found that only 20.5 % of the users of supplements were oriented by nutritionists and that 48% spend between R$51.00 and R$150.00 with these products. It is concluded that is large consumption of food supplements, without professional guidance appropriate, by frequenters of the academies.